Marketing Analysis of Purple Eggplant in the District of Likupang East Minahasa Utara - Merung, Yoseph Arteurt; Juniasih, Ida Ayu Komang; Pontoan, Karen A.; Kalalo, Marvil (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze, margin and marketing efficiency of purple eggplant at Yayasan Sander Batuna, East Likupang district. The data analysis technique used in this research is descriptive method. To analyze the variables in this study using margin analysis and marketing efficiency. The results show that the marketing channels in the foundation are farmers-retailers-consumers. The marketing margin obtained is Rp.5.455 /Kg and the value of farmer's shares is 45.45%, this shows that marketing cannot be said to be efficient.